Effect of Mg2+ co‐doping on the scintillation performance of LuAG:Ce ceramics. Issue 1 (5th November 2013) - Liu, Shuping; Feng, Xiqi; Zhou, Zhiwei; Nikl, Martin; Shi, Yun; Pan, Yubai
Abstract Ce‐doped Lu3Al5O12 optical ceramics co‐doped with Mg2+ are fabricated by solid‐state reaction method and further optimized by an air‐annealing process. Mg2+ co‐doping leads to a significant decrease of thermoluminescence intensity above room temperature and an increase of scintillation light yield (LY) value and fast component content even if the overall scintillation efficiency decreases. Scintillation LY of ∼21900 ph/MeV has been achieved with a short shaping time of 1 μs, and the ratio of LY values for 1 μs and 10 μs shaping times was as high as 79%. The acceleration of scintillation response induced by Mg2+ co‐doping and the role of Ce4+ ions in the scintillation mechanism are discussed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)